Urban governance under the Ottomans
1 online resource (xii, 238 pages)
Keywords: “Urban Governance under the Ottomans focuses on one of the most pressing topics in this field, namely the question of why cities formerly known for their multiethnic and multi-religious composition became increasingly marked by conflict in the 19th century. This collection of essays represents the result of an intense process of discussion among many of the authors, who have been invited to combine theoretical considerations on the question sketched above, with concrete case studies based upon original archival research. From Istanbul to Aleppo, and from the Balkans to Jerusalem, what emerges from the book is a renewed image of the imperial and local mechanisms of coexistence, and of their limits and occasional dissolution in times of change and crisis.Raising questions of governance and changes therein, as well as epistemological questions regarding what has often been termed 'cosmopolitanism', this book calls for a closer investigation of incidents of both peaceful coexistence, as well as episodes of violence and conflict. A useful addition to existing literature, this book will be of interest to scholars and researchers in the fields of Urban Studies, History and Middle Eastern Studies“--